(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Approximately 14 million people are employed in various capacities by India’s fisheries and aquaculture industries, which also contribute to agricultural exports and provide nutritional security for the food basket. Due to its varied aquatic resources, the nation has consistently increased its fish production since gaining its independence. This industry, which accounts for 6.3% of the world’s fish production, makes up 1.1% of the GDP and 5.15 percent of the GDP from agriculture. In recent years, there has been an increase of emerging and re-emerging diseases that result in significant economic losses for various global aquaculture industries. Rapid identification, characterization, and diagnosis of the causal agents and risk factors are essential for the development of efficient management methods aimed at reducing the detrimental effects of these disorders. Although the rapid development of advanced molecular techniques in aquaculture has diverted consumers’ and researchers’ attention from fundamental characterization methods, the latter remain extremely important. It is believed that diseases and epizootics represent significant obstacles to sectoral development and aquaculture production growth. The sector is currently dealing with global illness challenges as a result of a number of reasons. These consist of the subsequent items: (a) heightened commerce and market globalization; (b) intensification of fish farming methods through the movement of aquaculture species, feed, and related products; (c) introduction of new or alien species for the development of aquaculture.